Photo-Fenton degradation of the herbicide tebuthiuron under solar irradiation: Iron complexation and initial intermediates - Silva, Milady R. A. [UNESP]; Vilegas, Wagner [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The complexation of iron ions with the herbicide tebuthiuron (TBH), during a solar photo-Fenton process, was investigated using cyclic voltammetry with a glassy carbon electrode. An oxidation peak was observed at +0.64 V after addition of Fe(NO(3))(3) to TBH solution, indicating the formation of a Fe-TBH complex, which was not observed in the presence of ferrioxalate or citrate complexes. This complexation hinders photoreduction of Fe(III), and consequently TBH degradation. The main degradation route, in the presence or absence of citric acid (in the latter case with Fe(NO(3))(3) only), is initiated by the hydroxylation of a terminal methyl group of the urea, indicating an identical degradation mechanism. Hydroxylation of the central methyl of urea, and of the tert-butyl group, was also observed after extended irradiation periods in the presence of citric acid, but was not observed in the presence of Fe(NO(3))(3), due to a slower degradation rate in the absence of the citrate complex. No intermediate, generated from opening of the thiadiazole ring, was identified under the various different conditions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Iron complex; LC-MS; Intermediates; Voltammetry